'A long meandering slide': Feminist critique, genderqueerness, sexual agency and Crip subjectivity in Stephen Dwoskin's late works. (1st April 2022) - Chamarette, Jenny
Stephen Dwoskin was a prolific experimental filmmaker from the mid-1960s until his death in 2012. Commonly associated with the New York underground film scene and the London Filmmakers' Co-Op, which he co-founded in 1966, Jewish-American Dwoskin was also a childhood survivor of polio and a disability rights activist. Though an enduring oral legacy of feminist criticism of Dwoskin's work remains since the 1980s, Dwoskin's later work from the 1990s and 2000s is acutely understudied. In this article, I recontextualize earlier feminist positions in light of the 'cripping' of sexuality and gender proposed by recent critical disability studies, applied to two of Dwoskin's later works. Adopting archival evidence of feminist critique, feminist art histories and Crip approaches to sexuality, I examine androgyny and genderqueerness in Dwoskin's photomontages from Ha, Ha! La Solution Imaginaire (1993) and conflations of critical medical and BDSM-structured care in the film Intoxicated by My Illness (2001). I conclude that Dwoskin's work invites rich epistemological re-evaluation of both feminist critique and entrenched sociocultural conceptions of gendered subjectivity, intimacy and sexual agency.